The Importance of Urban Transportation, Managements and Strategies for Sustainable City - Süleyman Ay (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
In urban planning, the need for sustainable solutions is increasing day by day to facilitate and improve human life. With the developing technology, cities are tried to be transformed into sustainable cities by using smart city technologies. This article is about current problems in urban transportation planning and new developments. It is also an introduction to the subject. Papers on this issue emphasize how physical mobility is still an important priority for urban life. Five features have been identified regarding emerging urban transport, management and strategies. The first descriptive feature, the relationship between land use and transportation. The second is sustainable urban mobility, which estimates future generations and resources to improve the quality of life in cities by prioritizing physical and biological health. The third feature is the concept of accessibility and mobility in urban and pedestrian. The fourth feature is the concept of “road diet” that managers use persistently but do not succeed in. Urban transport planning is a communication-oriented activity and new transport services in relation to other professions and policy sectors. The cities, which are exemplified numerically and visually, have been selected among the cities which may be examples to the other developing cities of the world.